Study on the Knowledge, Attitude, and Practice (KAP) of Nursing Staff and Influencing Factors on COVID-19 - Wen, Xin; Wang, Fan; Li, Xiuyang; Gu, Hua (Frontiers in Public Health, 2021)
The aim of this study is to investigate the knowledge, attitude, and practice (KAP) on Coronavirus Disease 2019 (COVID-19) care among nursing staff and analyze its influencing factors. The survey was conducted on February 18, 2020, among 7,716 voluntary participants from 143 medical institutions in Zhejiang, China. The findings indicated that KAP of nursing staff scored well. However, the accuracy of psychological nursing knowledge was much lower, 14.3% only. Nursing staff working in isolation wards have higher knowledge (OR = 1.776, 95% CI: 1.491–2.116), attitude (OR = 1.542, 95% CI: 1.298–1.832), and practice (OR = 1.902, 95% CI: 1.590–2.274) scores than those in general wards. In terms of KAP, nursing staff with working experience ≤ 10 years scored lower than those with working experience ≥ 20 years, with OR values of 0.490 (95% CI: 0.412–0.583), 0.654 (95% CI: 0.551–0.775), and 0.747 (95% CI: 0.629–0.886), respectively. It is necessary to take measures to enhance the training on COVID-19, especially for KAP of junior nurses in general wards.